A Toxocara cati eggs concentration method from cats’ faeces, for experimental and diagnostic purposes - Cardillo, Natalia Marina (2014)
Toxocariosis is a zoonotic parasite infection worldwide distributed, now considered a neglected disease associated to poverty. For experimental infection in animals and to develop the diagnosis in humans it is necessary to obtain large number of Toxocara spp. larval eggs. Toxocara cati eggs recovered percentage from faeces of infected cats was determined employing a novel egg concentration method. The McMaster egg counting technique and the concentration method were applied on 20 positive cats’ sample faeces obtained from naturally infected cats. The mean percentage of eggs recovered by the concentration method was 24.37% higher than the count obtained by McMaster egg counting technique. The main advantage of this method is that it can be obtained a small final volume with a high number of recovered eggs and a good quality inoculum for experimental and diagnostic purposes.